The Situation of Immigrant Students in Latin American School: An Exploration from the Perspectives of Inclusion and Interculturality - Merino Solari, Renatto (2025)
The essay aims to explore the situation of immigrant students in Latin American schools focusing on two aspects: the factors that limit an inclusive and intercultural educational practice and the ways in which students respond to the challenges posed by their school experience. The conclusion is that two contradictory conceptions/practices of education coexist in Latin American educational systems. One, which understands education as a public good that can be universalized under the same conditions for all; the other, which conceives education as a limited good in relation to the economic, social and cultural possibilities of families, a model imposed by the neoliberal shift that took place in the region. This tension has a direct impact on school life and is manifested in two paradoxical situations: i) states recognize that they must guarantee education for all, but at the same time, they promote the expansion of a segregating educational market; ii) the incorporation of inclusion and intercultural approaches in national policies and curricula coexist with discriminatory practices and non-recognition of cultural identity.Consequently, immigrant students find themselves in a situation of permanent tension between forms of “subordinate inclusion” and the struggle for recognition of their rights and respect for their cultural particularities.